Plasmacytoid Myoepithelioma of the Hard Palate - Çetin, Mehmet Ali; İkincioğulları, Aykut; Köseoğlu, Sabri; Özdaş, Talih; Ensari, Serdar; Dere, Hüseyin (Fırat University, 2012)
Myoepithelioma is extremely rare benign tumor of salivary glands. It represents less than 1% of all salivary gland tumors. Myoepithelioma is diagno-sed by histopathological evaluation. In this article, a 53 years old female patient with myoepithelioma of the hard palate is presented.

Miyoepiteliyoma tükürük bezlerinin oldukça nadir görülen benign tümörüdür ve tüm tükürük bezi tümörlerinin yaklaşık %1'den daha azını oluşturur. Miyoepiteliyoma tanısı histopatolojik inceleme ile konulur. Bu yazıda, 53 yaşında sert damakta plazmositoid miyoepiteliyoma tanısı konulan bayan hasta sunuldu.
Sert Damakta Plazmositoid Miyoepiteliyoma